Female breast cancer in Central and South America. (September 2016) - Di Sibio, Alejandro; Abriata, Graciela; Forman, David; Sierra, Mónica S.
Abstract: Rationale and objective: The burden of breast cancer has increased worldwide. Breast cancer mortality has been increasing in Central and South America (CSA) in the last few decades. We describe the current burden of breast cancer in CSA and review the current status of disease control. Methods: We obtained regional- and national-level incidence data from 48 population-based cancer registries in 13 countries and cancer deaths from the WHO mortality database for 18 countries. We estimated world population age-standardized incidence and mortality rates per 100, 000 person-years for 2003–2007 and the estimated annual percentage change to describe time trends. Results: In the most recent 5-year period, Argentina, Brazil, and Uruguay had the highest incidence rates (67.7–71.9) and Bolivia and El Salvador had the lowest (7.9–12.7). For most countries, mortality rates were ≤12.3, except in Uruguay, Argentina and Cuba (14.9-20.5). Age-specific rates increased after the age of 40–50 years and reached a maximum after age 65 years (mean age at diagnosis 56–62 years). Most countries have developed national screening guidelines; however, there is limited capacity for screening. Conclusion: The geographic variation of breast cancer rates may be explained by differences in the prevalence of reproductive patterns, lifestyle factors, early detection, and healthcare access. Extending early-detection programs is challenging because of inequalities in healthcare access and coverage, limited funding, and inadequate infrastructure, and thus it may not be feasible. Given the current status of breast cancer in CSA, data generated by population-based cancer registries is urgently needed for effective planning for cancer control.